2021
DOI: 10.1038/s42003-021-02799-3
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic receptors mediate nitrogenous waste avoidance in Drosophila melanogaster

Abstract: Ammonia and its amine-containing derivatives are widely found in natural decomposition byproducts. Here, we conducted biased chemoreceptor screening to investigate the mechanisms by which different concentrations of ammonium salt, urea, and putrescine in rotten fruits affect feeding and oviposition behavior. We identified three ionotropic receptors, including the two broadly required IR25a and IR76b receptors, as well as the narrowly tuned IR51b receptor. These three IRs were fundamental in eliciting avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Therefore, we tested a repertoire of putative taste receptors (31 candidate Ir and nine candidate Gr loss‐of‐function mutants) via electrophysiology on L4 and L6 sensilla to elucidate the vitamin C receptors (Fig 2A and B). This included the broadly required Ir25a and Ir76b (Zhang et al , 2013; Chen & Amrein, 2017; Ganguly et al , 2017; Lee et al , 2018; Dhakal et al , 2021; Shrestha & Lee, 2021a; Xiao et al , 2022; Aryal et al , 2022a). Ir7a and Ir62a are required for sensing acetic acid and Ca 2+ , respectively (Lee et al , 2018; Rimal et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we tested a repertoire of putative taste receptors (31 candidate Ir and nine candidate Gr loss‐of‐function mutants) via electrophysiology on L4 and L6 sensilla to elucidate the vitamin C receptors (Fig 2A and B). This included the broadly required Ir25a and Ir76b (Zhang et al , 2013; Chen & Amrein, 2017; Ganguly et al , 2017; Lee et al , 2018; Dhakal et al , 2021; Shrestha & Lee, 2021a; Xiao et al , 2022; Aryal et al , 2022a). Ir7a and Ir62a are required for sensing acetic acid and Ca 2+ , respectively (Lee et al , 2018; Rimal et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown a requirement for three members of the Ir family (Ir51a, Ir25a and Ir76b) in activation of bitter neurons to nitrogenous waste compounds. 33 However, a determination of whether the observed inhibition is dependent on these or any other chemosensory receptors, or whether it is mediated by some other aspects of cellular function, awaits further molecular genetic investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, labellum and legs are the major taste organs, which mediate a major role in contact chemosensation in insects. The full benefit of this behavioral assay is realized when performed in combination with an electrophysiological assay that measures tastant-induced action potentials in gustatory receptor neurons (tip recordings) ( Aryal et al., 2022 ; Dhakal et al., 2021 ; Shrestha and Lee, 2021a ).…”
Section: Before You Beginmentioning
confidence: 99%
“…, 2022). Complete preference is indicated by P.I values of 1.0 and -1.0 while a P.I value of 0 indicates the absence of a bias between the two food choices ( Aryal et al., 2022 ; Dhakal et al., 2021 ; Shrestha and Lee, 2021b ; Shrestha et al., 2022 ).
Figure 1 Binary food choice assay (A) Photograph of 72-well microtiter plate containing red dye and blue dye mixed food for a binary food choice assay.
…”
Section: Before You Beginmentioning
confidence: 99%
See 1 more Smart Citation